(untitled) (TAJ: Journal of Teachers Association, 2019)
Objective: To determine the prevalence of cervical intra epithelial neoplasia (CIN) among sexually active married women in Rajshahi division of Bangladesh. Study Design: It is a prospective cross sectional type descriptive study. Place and Duration: This study is population based & carried out in 4 selected Upazilla from 4 different districts of Rajshahi Division. Total 1050 patient were enrolled in the study. Study period was 6 months from 1st December 2014 to 31st May 2015. Subject and Method: All sexually active woman between age group 25 to 55 years in selected Upazilla. In UHC of preselected Upazilla who fulfilled the inclusion criteria enrolled in the study after taking the consent. Frequency & risk factors for CIN were analyzed after entering in predesigned proforma. Result: During study period of 6 months among 1050 enrolled patients 90 patient were VIA positive and 91 patients were colposcopically abnormal and among these 33 patients were CIN positive & 58 patients had chronic cervicitis with or without squamous metaplasia. Mean age of CIN positive were 36.75 years, 92.2% patient were housewife & 7.8% patient were service holder and in 64.6% patients education level up to XII class, in 55.5% patients husband was day labour from poor socioeconomic condition. Conclusion: VIA and Colposcopy can differentiate a normal cervix from a precancerous cervix with reasonable accuracy. Till now, a good number of studies had been carried out in different countries of world & it is now well established that sensitivity of the test is very good. From the present study we can conclude that it will give very good information about the prevalence of CIN in our country and by follow up study this might help us in reducing the incidence of carcinoma cervix. TAJ 2018; 31(2): 1-5